Azo-Hydrazone Tautomerism and Antimicrobial activity of New substituted Imidazolines and Perimidines (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Two new series of 2-{1-[(substitutedphenyl)-hydrazono]-2-oxo-2-phenyl-ethyl}-5,5-diphenyl-3,5-dihydro-imidazol-4-one Â andÂ  (1H-Perimidin-2-yl)-[(substitutedphenyl)-hydrazono]-acetic acid ethyl ester were prepared by coupling the diazonium salt of aniline and its derivatives with 2-(2-oxo-2-phenyl-ethylidene)-5,5-diphenyl-imidazolidin-4-one or ethyl 3-dimethylamino-2-(1H-perimidin-2-yl)-propenoate in ethanolic sodium hydroxide solution. The structures of all the newly synthesized compounds were confirmed by spectral (IR, 1H NMR, mass) spectra , and X-ray crystallographic and elemental analyses. Also, the azo-hydrazone tautomerism of these compounds was discussed. In addition, all the newly synthesized compounds were screened for their antibacterial and antifungal activity and the results obtained indicated that some of these compounds exhibited excellent activity.